Development of a Japanese version of the Autobiographical Recollection Test: convergent validity with self-reported scales and memory details. Issue 10 (26th November 2022) - Matsumoto, Noboru; Kiire, Satoru; Ikeda, Hiroka
ABSTRACT: While numerous studies have examined the characteristics of specific autobiographical memories, until recently, no questionnaire has asked how individuals remember their past in general. We developed a Japanese version of the Autobiographical Recollection Test (ART), which consists of seven components (vividness, narrative coherence, reliving, rehearsal, scene, visual imagery, and life story relevance) and surveys the general characteristics of autobiographical remembering. Confirmatory factor analysis and item response theory showed that the Japanese version of the ART had sufficient psychometric properties and generally correlated as hypothesised with self-report questionnaires as a measure of convergent validity. While the short version of the Japanese ART correlated positively with the internal details (episodic elements) of autobiographical narratives, the full version did not correlate with internal details. We discuss the use of ART for future research examining individual and cultural differences in autobiographical remembering.